conindex: Estimation of concentration indices - O'Donnell, Owen; O'Neill, Stephen; Van Ourti, Tom; Walsh, Brendan (The Stata journal, 2016)
Concentration indices are frequently used to measure inequality in one variable over the distribution of another. Most commonly, they are applied to the measurement of socioeconomic-related inequality in health. We introduce a user-written Stata command which provides point estimates and standard errors of a range of concentration indices. The command also graphs concentration curves (and Lorenz curves) and performs statistical inference for the comparison of inequality between groups. The article offers an accessible introduction to the various concentration indices that have been proposed to suit different measurement scales and ethical responses to inequality. The command's capabilities and syntax are demonstrated through analysis of wealth-related inequality in health and healthcare in Cambodia.